Label-free confocal iSCAT microscopy on live cells - Küppers, Michelle; Albrecht, David; Kashkanova, Anna; Lühr, Jennifer; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2021)
Confocal interferometric scattering microscopy (iSCAT) enables the label-free visualization of cellular organelles and tracking of nanoscopic matter such as intracellular vesicles and viruses.
CRIS-Team Scopus Importer:2021-12-03